Photoactivation Approaches Reveal a Role for Rab11 in FGFR4 Recycling and Signalling. (31st March 2014) - Haugsten, Ellen M.; Brech, Andreas; Liestøl, Knut; Norman, Jim C.; Wesche, Jørgen
<x xml:space="preserve">Abstract</x> Fibroblast growth factor receptor 4 (FGFR4) plays important roles during development and in the adult to maintain tissue homeostasis. Moreover, overexpression of FGFR4 or activating mutations in FGFR4 has been identified as tumour‐promoting events in several forms of cancer. Endocytosis is important for regulation of signalling receptors and we have previously shown that FGFR4 is mainly localized to transferrin‐positive structures after ligand‐induced endocytosis. Here, using a cell line with a defined pericentriolar endocytic recycling compartment, we show that FGFR4 accumulates in this compartment after endocytosis. Furthermore, using classical recycling assays and a new, photoactivatable FGFR4‐PA‐GFP fusion protein combined with live‐cell imaging, we demonstrate that recycling of FGFR4 is dependent on Rab11. Upon Rab11b depletion, FGFR4 is trapped in the pericentriolar recycling compartment and the total levels of FGFR4 in cells are increased. Moreover, fibroblast growth factor 1 (FGF1)‐induced autophosphorylation of FGFR4 as well as phosphorylation of phospholipase C (PLC)‐γ is prolonged in cells depleted of Rab11. Interestingly, the activation of mitogen‐activated protein kinase and AKT pathways were not prolonged but rather reduced in Rab11‐depleted cells, indicating that recycling of FGFR4 is important for the nature of its signalling output. Thus, Rab11‐dependent recycling of FGFR4 maintains proper levels of FGFR4 in cells and regulates FGF1‐induced FGFR4 signalling. <inline-graphic xlink:href="ark:/27927/pgh4dc4k" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />